Qualitative Analysis of Emotions: Fear and Thrill - Buckley, Ralf C. (Frontiers in Psychology, 2016)
People can speak, and this provides opportunities to analyse human emotions using perceived experiences communicated via language, as well as through measurement and imaging techniques that are also applicable to other higher animal species. Here I compare four qualitative methodological approaches to test if, and how, thrill depends on fear. I use 8 high-risk, high-skill, real-life outdoor adventure recreation activities to provide the test circumstances. I present data from: >4000 person-days of participant observation; interviews with 40 expert practitioners; retrospective autoethnography of 50 critical incidents over 4 decades; and experimental autoethnography of 60 events. Results from different methods are congruent, but different approaches yield different insights. The principal findings are as follows. Individuals differ in their fear and thrill responses. The same individual may have different responses on different occasions. Fear boosts performance, but panic causes paralysis. Anxiety or apprehension prior to a risky action or event differs from fear experienced during the event itself. The intensity of pre-event fear generally increases with the immediacy of risk to life, and time to contemplate that risk. Fear must be faced assessed and overcome in order to act. Thrill can occur either during after a high-risk event. Thrill can occur without fear, and fear without thrill. Below a lower threshold of perceived risk, thrill can occur without fear. Between a lower and upper threshold, thrill increases with fear. Beyond the upper threshold, thrill vanishes but fear remains. This there is a sawtooth relation between fear and thrill. Perceived danger generates intense focus and awareness. Fear and other emotions can disappear during intense concentration and focus. Under high risk, the usual emotional sequence is fear before the action or event, then focus during the action or event, then thrill, relief, or triumph afterwards. The emotionless state persists only during the most intense concentration. For events long enough to differentiate time within the events, fear and thrill can arise and fade in different fine-scale sequences.